Perawatan Periodontitis pada Puskesmas Sumbersari, Puskesmas Wuluhan dan RS Bondowoso - Kiswaluyo Kiswaluyo (Fakultas Kedokteran Gigi Universitas Jember, 2013)
Dental and oral diseases are the first on the list of the top 10 common diseases that complaint by Indonesian. Periodontitis is one of dental and oral diseases that usually found in Indonesian. Periodontitis is dental supporting tissue inflammation that caused by certain microorganism and caused periodontal tissue destruction. The major etiology of periodontitis is plaque bacteria. The aim of this study was to know periodontitis treatment in public health center care (Puskesmas) Sumbersari, Wuluhan and Bondowoso Hospital. This study was retrospective descriptive. Sampling technique used secondary data, sampling based on previous data in Puskesmas Sumbersari, Wuluhan and Bondowoso Hospital. Population of this study was patient who came in Sumbersari, Wuluhan and Bondowoso Hospital, about 812 patients. The samples were patients who diagnosed periodontitis, about 199 patients. The result showed that periodontitis was the most oral diseases that found in Puskesma Sumbersari, Wuluhan and Bondowoso Hospital. Puskesmas Sumbersari had the most incidences of periodontitis, it was about 120 patients. The most treatment of periodontitis was periodontal medication and tooth extraction. The conclusion described there was difference treatment in each public health care center and hospital.